Business services as actors of knowledge transformation and diffusion: some empirical findings on the role of KIBS in regional and national innovation systems - Emmanuel Muller; Andrea Zenker (Fraunhofer Institute for Systems and Innovation Research ISI, 2001)
Over the last years, there has been a significant increase in the attention paid to the activities of knowledge-intensive business services (KIBS). KIBS produce and duffus knowledge, which is crucial for innovation processes. The paper gives an overview of the role and function of KIBS in innovation systems and their knowledge production, transformation and diffusion activities. Focusing on innovation interactions between manufacturing small- and medium-sized enterprises (SMEs) and KIBS; the empirical analyses gasps KIBS in position in five contexts. The analysis leads to the conclusion that innovation activities links SMEs and KIBS through the process of knowledge and diffiusion.
urn:nbn:de:0011-n-59157
Keywords: 330; Business services; Knowledge; Innovation; Knowledge transfer; Innovation diffusion; Supplier-customer relationship; Small and medium-sized industry; Germany; Unternehmensdienstleistung; Wissen; Innovation; Wissenstransfer; Innovationsdiffusion; Lieferanten-Kunden-Beziehung; Mittelständische Industrie; Theorie; Deutschland